Porte-chaises and Gazebos in the Traditions of European Horse-Drawn Transport of the Baroque Era - Olha Shkolna; Ostap Kovalchuk (Культура і мистецтво у сучасному світі, 2024)
The aim of the article is to determine the constructive, compositional and artistic features of porte-chaises and gazebos in the European proto-design of the Baroque era. Results. It has been found that among the horse-drawn transport of the Baroque period in European proto-design, a special place was occupied by carriage carriers, which were carried by special porters, following the example of ancient oriental prototypes. The author reveals that this tradition was initiated under the influence of interaction with the Indian Raj and other representatives of the Eastern establishment and developed among the high society circles of nobility in England, Spain, Italy, and France as a reflection on colonial ambitions in society. The scientific novelty of the study is related to the analysis of constructive, compositional and artistic features of gazebos and porte-chaises in the European tradition of horse-drawn transport of the seventeenth and eighteenth centuries on the example of monuments that have been preserved or recorded by artists. Conclusions. It has been proved that the production of baroque portable carriages such as porte-chaises and gazebos was carried out by individual specialists-woodcarvers. They knew how to combine metal and wooden structures of the product’s frame, as well as how to design the “salon-cabin” using different types of leather and drapery fabrics. The ways of external decoration of such objects with a representative heraldic coat of arms compositions, bouquets of flowers, and plot motifs are outlined. The article illustrates the varieties of porte-chaises, gazebos, sedan chairs, palanquins, and sigettes (sigetter, “vastasi di cinga”) typical of the seventeenth and eighteenth centuries in the works of European painters.